The Association of Serum Vitamin D Levels with Lung Function, Symptom Severity, and Exacerbations in Stable COPD Patients - Yusuf, Nurrahmah; Mekasari, Chelsy; Dianova, Sri; Priyanto, Herry; Yanti, Budi (Queeva Publishing, 2024)
Background: Chronic obstructive pulmonary disease (COPD) is a significant health burden associated with a decrease in quality of life. Patients with the disease often have a deficiency of Vitamin D, a fat-soluble vitamin important for respiratory health. A previous study suggested an association between low vitamin D levels and poor lung function, as well as increased exacerbation, and more severe COPD symptom. Therefore, this study aimed to assess serum vitamin D levels in stable COPD patients and explore association with lung function, symptom severity, and frequency of exacerbation. Methods: This was a cross-sectional study conducted from May to July 2023 at Lung Polyclinic of Dr. Zainoel Abidin Regional General Hospital (RSUDZA) Banda Aceh. A total of 30 subjects selected based on specific inclusion and exclusion criteria were included. Results: The results showed that the mean serum vitamin D level was 26.25 ng/mL, with 56.7% of subjects showing vitamin D insufficiency. Statistical analysis showed p-values of 0.58, 0.637, 0.12, and 0.98 for lung function, exacerbation, COPD Assessment Test (CAT), and Modified Medical Research Council (mMRC) dyspnoea scale respectively, indicating no significant association between vitamin D levels and these outcomes. Potential confounding factors include unassessed variables such as medication use, educational background, and psychological status. Conclusion: This study found no significant association between serum vitamin D levels and lung function, symptom severity, or frequency of exacerbation in stable COPD patients. Further studies with a larger sample size and extended follow-up are needed to confirm these results and explore additional influencing factors.